Principles of capitalistic commodity production - Fritz Helmedag (Intervention. European Journal of Economics and Economic Policies, 2012)
The causal structure of capitalistic commodity production can be revealed by notionally separating total output into two categories: 'necessaries' bought by employees, and the rest constituting society's surplus. The rate of profit is determined in the wage good industry and becomes the system?s key variable. In association with demand for 'luxuries' it governs the respective amount of profit accruing to the two sectors as well as the corresponding employment. The consequences for economic policy contradict predominant recipes.
Keywords: A10; B12; E10; 330; effective demand; employment; income shares; labour theory of value; rate of exploitation; rate of profit; rate of surplus value